Exploring the diversity of Gracillariidae (Lepidoptera) in South Africa: host plants, distribution, and DNA barcoding analysis, with the description of nine new species - Triberti, Paolo; Staude, Hermann; Sharp, Ian; Lopez-Vaamonde, Carlos (Zootaxa, 2024)
Despite relatively extensive historical exploration being carried out on Lepidopteran fauna of South Africa, leaf-mining micromoths of the family Gracillariidae remain a source of discovery, with many new species awaiting description. In the present work, 32 gracillariid species from South Africa are treated. For each species, hostplant and distribution information is provided, supplemented by taxonomic and molecular analysis where necessary. Nine species are described here as new to science: Ectropina spirostachydis sp. nov., Leucocercops curatellifoliae sp. nov., Phodoryctis tephrosiella sp. nov., Telamoptilia cordati sp. nov., Phyllonorycter pseudogrewiella sp. nov., Cameraria melhaniella sp. nov., Phyllocnistis magalismontani sp. nov., P. allisonae sp. nov. and P. faureae sp. nov. Sixteen host plant species are reported for the first time for the family Gracillariidae: Searsia pyroides (Anacardiaceae), Parinari curatellifolia (Chrysobalanaceae), Combretum zeyheri, Terminalia sericea (Combretaceae), Euclea divinorum (Ebenaceae), Spirostachys africana (Euphorbiaceae), Peltophorum africanum, Tephrosia rhodesica, Schotia brachypetala (Fabaceae), Cryptocarya transvaalensis (Lauraceae), Melhania acuminata (Malvaceae), Syzygium guineense (Myrtaceae), Ochna pretoriensis (Ochnaceae), Protea rubropilosa, Faurea saligna (Proteaceae), Englerophytum magalismontanum (Sapotaceae). Caloptilia mwamba De Prins, 2015 is recorded for the first time in South Africa.